Nup153 Interacts with Sox2 to Enable Bimodal Gene Regulation and Maintenance of Neural Progenitor Cells - Toda, Tomohisa; Hsu, Jonathan Y.; Linker, Sara B.; Hu, Lauren; Schafer, Simon T.; Mertens, Jerome; Jacinto, Filipe V.; Hetzer, Martin W.; Gage, Fred H. (Cell Stem Cell, 2017)
Neural progenitor cells (NeuPCs) possess a unique nuclear architecture that changes during differentiation. Nucleoporins are linked with cell-type-specific gene regulation, coupling physical changes in nuclear structure to transcriptional output; but, whether and how they coordinate with key fate-determining transcription factors is unclear. Here we show that the nucleoporin Nup153 interacts with Sox2 in adult NeuPCs, where it is indispensable for their maintenance and controls neuronal differentiation. Genome-wide analyses show that Nup153 and Sox2 bind and co-regulate hundreds of genes. Binding of Nup153 to gene promoters or transcriptional end sites correlates with increased or decreased gene expression, respectively, and inhibiting Nup153 expression alters open chromatin configurations at its target genes, disrupts genomic localization of Sox2, and promotes differentiation in vitro and a gliogenic fate switch in vivo. Together, these findings reveal that nuclear structural proteins may exert bimodal transcriptional effects to control cell fate. Toda et al. demonstrate that the nucleoporin Nup153 interacts and cooperates with Sox2 to regulate the cellular state of neural progenitor cells. Nup153 binds both the 5′ and 3′ ends of genes, and the direction of gene regulation by Nup153 varies with the binding position of Nup153.
CRIS-Team Scopus Importer:2022-09-26
Keywords: adult neurogenesis; bimodal gene regulation; cell fate; key transcription factors; neural differentiation; neural progenitor cells; nucleoporins; Nup153; Sox2; spatial transcriptional regulation